Validation and Application of a Dried Blood Spot Ceftriaxone Assay - Page-Sharp, M.; Nunn, T.; Salman, S.; Moore, B.; Batty, Kevin; Davis, T.; Manning, L. (2015)
Dried blood spot (DBS) antibiotic assays can facilitate pharmacokinetic/pharmacodynamic (PK/PD) studies in situations where venous blood sampling is logistically and/or ethically problematic. In this study, we aimed to develop, validate, and apply a DBS ceftriaxone assay. A liquid chromatography-tandem mass spectroscopy (LC-MS/MS) DBS ceftriaxone assay was assessed for matrix effects, process efficiency, recovery, variability, and limits of quantification (LOQ) and detection (LOD). The effects of hematocrit, protein binding, red cell partitioning, and chad positioning were evaluated, and thermal stability was assessed. Plasma, DBS, and cell pellet ceftriaxone concentrations in 10 healthy adults were compared, and plasma concentration-time profiles of DBS and plasma ceftriaxone were incorporated into population PK models. The LOQ and LOD for ceftriaxone in DBS were 0.14 mg/liter and 0.05 mg/liter, respectively. Adjusting for hematocrit, red cell partitioning, and relative recovery, DBS-predicted plasma concentrations were comparable to measured plasma concentrations (r > 0.95, P < 0.0001), and Bland-Altman plots showed no significant bias. The final population PK estimates of clearance, volume of distribution, and time above threshold MICs for measured and DBS-predicted plasma concentrations were similar. At 35°C, 21°C, 4°C, −20°C, and −80°C, ceftriaxone retained >95% initial concentrations in DBS for 14 h, 35 h, 30 days, 21 weeks, and >11 months, respectively. The present DBS ceftriaxone assay is robust and can be used as a surrogate for plasma concentrations to provide valid PK and PK/PD data in a variety of clinical situations, including in studies of young children and of those in remote or resource-poor settings.